Bacterial Growth at Low Pressure: A Short Review - Verseux, Cyprien (Frontiers in Astronomy and Space Sciences, 2020)
Biological life-support systems could greatly increase the sustainability of crewed missions to the Moon or Mars. Understanding how bacteria react to hypobaria is critical to their optimization: if enclosed within crewed compartments, microbial modules may be exposed to the lower-than-Earth atmospheric pressure considered for future space vehicles and habitats and, if deployed outside, they would best rely on a low pressure to minimize both engineering constraints and risks of leakage. Bacterial behavior at low pressures is of relevance to other fields as well, both within astrobiology (e.g., habitability and planetary protection) and outside of it (e.g., aerobiology and food preservation). Unfortunately, while microbial survival under vacuum has been largely investigated, little work has focused on metabolism at low but growth-permissive pressures. Nonetheless, recent studies brought some insights. Limits were outlined: a few bacterial species can grow just above water's triple point, more can multiply down to around 25 mbar, and shifting pressure within 100 mbar to 1 bar seems not to largely affect growth of most species when the partial pressures of metabolizable gases are not limiting. Some mediating mechanisms have been proposed: hypobaria can affect bacteria by desiccation, via a reduced availability of specific gases, and through various other physico-chemical effects, interdependent and dependent on other environmental factors. A limited number of studies also gave insights into how bacteria cope with low pressure, and how much they can adapt to it. But, overall, much remains to be discovered on bacterial growth under hypobaric conditions.